2017
DOI: 10.14740/cr631w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Tp-Te Interval, QTc and P-Wave Dispersion in Patients With Coronary Artery Ectasia

Abstract: BackgroundCoronary artery ectasia (CAE) is defined as a diffuse dilatation of the diameter of the ectatic segment of the coronary artery, 1.5 times greater than that of the adjacent segment. The Tp-Te interval, P-wave and QTc dispersions are relatively new electrocardiographic markers associated with an increased risk of developing arrhythmias. Despite CAE increasing in prevalence in recent years, there is a sparsity of data available about its arrhythmogenic effect. The aim of the study was to evaluate QTc, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Other important indices like QT, QTc, Tp-Te/QT, Tp-Te/QTc, Tp-Tec/QTc didn’t show any significant difference between groups. When looking into results more precisely in tables, our mean Tp-Te/ QT and Tp-Te/ QTc values in all groups were found higher than important cutoff levels in some trials [8], [24], [31], [32], [34]. But after careful examination, some indices were found meaningful higher than accepted cutoff points according to some trials, mean Tp-Te/QT level in our HFmrEF patients was higher than patients with BS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other important indices like QT, QTc, Tp-Te/QT, Tp-Te/QTc, Tp-Tec/QTc didn’t show any significant difference between groups. When looking into results more precisely in tables, our mean Tp-Te/ QT and Tp-Te/ QTc values in all groups were found higher than important cutoff levels in some trials [8], [24], [31], [32], [34]. But after careful examination, some indices were found meaningful higher than accepted cutoff points according to some trials, mean Tp-Te/QT level in our HFmrEF patients was higher than patients with BS.…”
Section: Discussionmentioning
confidence: 98%
“…Conlon et al, found mean Tp-Te and Tp-Te/QT ratio significantly were prolonged in patients with coronary artery ectasia comparing to control group (Tp-Te: 95.5 ± 9.01 ms vs. 84 ± 5.62 ms and Tp-Te/QT: 0.22 ± 0.02 vs. 0.20 ± 0.01, P < 0.05 for all) [31]. Tenekecioglu et al, found mean Tp-Te, Tp-Te/QT and Tp-Te/QTc ratio were significantly higher in patients with coronary slow flow phenomenon (Tp-Te: 85 ± 13.7 ms vs. 74 ± 9.9 ms and Tp-Te/QT: 0.24 ± 0.03 vs. 0.20 ± 0.02 and Tp-Te/QTc: 0.20 ± 0.03 vs 0.17 ± 0.02 all of P -value < 0.001) [32].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Pd is an indicator for atrial fibrillation (AF) and the high Pd value in COVID-19 shows COVID-19 may be a predictor for the development of AF. Furthermore, autonomic system, endothelial dysfunction, and inflammatory response have an impact on p wave duration and dispersion 17,18 . The fact that autonomic imbalance affects intra-atrial and interatrial conduction times may be prone to atrial arrhythmias 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Kaneko and colleagues found an inverse correlation between the duration of moderate strength Tpeak-Tend with the degree of myocardial blush in patients with STEMI undergoing primary PCI. 31,32 Length Tpeak-Tend also studied the condition of the…”
Section: P-wave Dispersionmentioning
confidence: 99%